Expression of TRX1 optimizes the antitumor functions of human CAR T cells and confers resistance to a pro-oxidative tumor microenvironment - Balta, Emre; Janzen, Nina; Kirchgessner, Henning; Toufaki, Vasiliki; Orlik, Christian; Liang, Jie; Lairikyengbam, Divya; Abken, Hinrich; Niesler, Beate; Müller-Decker, Karin; Ruppert, Thomas; Samstag, Yvonne (Frontiers in Immunology, 2022)
Use of chimeric antigen receptor (CAR) T cells to treat B cell lymphoma and leukemia has been remarkably successful. Unfortunately, the therapeutic efficacy of CAR T cells against solid tumors is very limited, with immunosuppression by the pro-oxidative tumor microenvironment (TME) a major contributing factor. High levels of reactive oxygen species are well-tolerated by tumor cells due to their elevated expression of antioxidant proteins; however, this is not the case for T cells, which consequently become hypo-responsive. The aim of this study was to improve CAR T cell efficacy in solid tumors by empowering the antioxidant capacity of CAR T cells against the pro-oxidative TME. To this end, HER2-specific human CAR T cells stably expressing two antioxidant systems: thioredoxin-1 (TRX1), and glutaredoxin-1 (GRX1) were generated and characterized. Thereafter, antitumor functions of CAR T cells were evaluated under control or pro-oxidative conditions. To provide insights into the role of antioxidant systems, gene expression profiles as well as global protein oxidation were analyzed. Our results highlight that TRX1 is pivotal for T cell redox homeostasis. TRX1 expression allows CAR T cells to retain their cytolytic immune synapse formation, cytokine release, proliferation, and tumor cell-killing properties under pro-oxidative conditions. Evaluation of differentially expressed genes and the first comprehensive redoxosome analysis of T cells by mass spectrometry further clarified the underlying mechanisms. Taken together, enhancement of the key antioxidant TRX1 in human T cells opens possibilities to increase the efficacy of CAR T cell treatment against solid tumors.